Penentuan Program Pengembangan IKM Dengan Pendekatan Multi Criteria Decision Making: Perspektif Faktor Internal - Johan K Runtuk (President University, 2018)
Small and medium enterprises (SMEs) play a significant role for Indonesian economy. However, many SMEs have difficulty developing its business. The various SME development programs that are provided are generally less impactful, ineffective, and unsustainable. Therefore, a special study is needed to determine the development program for SMEs. This research integrates two methods in multi criteria decision making (MCDM), i.e. decision-making method of trial and evaluation laboratory (DEMATEL) and analytic network process (ANP) method to determine which internal factors that are most important for SMEs development. Based on the data obtained from the experts and the results of the analysis, internal factor that has biggest weight for the development of SMEs are managerial quality, investment, business owner characteristics, and entrepreneurial orientation; consecutively. Moreover, technology awareness and the determination and achievement of targets (sub-factor of managerial quality), technological development (sub-factor of investment), and membership/involvement in business/association groups (sub-factor of business owner characteristics) are significant factor for SMEs development. SMEs development programs should focus on improving these factors so that Indonesian SMEs can experience sustainable growth.Keywords: development programs, small and medium enterprises (SMEs), decision-making trial and evaluation laboratory (DEMATEL), analytic network process (ANP), internal factors.